A general model for trust management. (1st January 2011) - Al-Arayed, Dalal Ahmed; Sousa, João Pedro
General trust management (GTM) is a trust management model that resides on the decision maker's device. Like other trust models, it operates with minimal human intervention. However, GTM is different in its versatility which makes it applicable in multiple problem scenarios, for e.g., service provision, packet routing, content management and location disclosure. GTM provides a highly flexible solution, where individual users may leverage peer stereotyping to personalise their privacy policies in a scalable way. GTM can handle trust chains and is a fully functional trust model that handles storage of trust data, trust formation, trust dissemination and trust evolution.